Perlindungan Nasabah Bank Dari Tindakan Kejahatan Skimming Di Tinjau Dari Undang Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan. - Yulianti Yulianti (Widya Yuridika, 2020)
Bank Customer Protection is an effort to provide legal certainty to bank customers under Law No. 21 of 2011 on Financial Services Authority.Skiming crime is a crime of activity or attempt by a person to break into data from the magnetic tape of an ATM/Debit card so that the perpetrator can know the data from the victim illegally. The Financial Services Authority is an independent institution and free from the interference of other parties, which has the functions, duties, and authority of the arrangement, supervision, examination and investigation as intended in Law no. 21 of 2011. In addition to the strict application of the Law, the Bank must also provide customers with information and knowledge as to how to avoid skimming crimes.